Forced Labour and the System of Overburdening in the Interwar Middle Congo: Congolese Populations between Administrative Violence and Local Runaway Schemes, 1918–1948 - Belina, Céline; Keese, Alexander (International review of social history, 2025)
Forced labour in the Middle Congo was characterized in the interwar period by, on the one hand, a declining role of the notorious French concession companies, and, on the other hand, the growing importance of forced recruitment and forced labour orchestrated by the colonial state. The article attempts to analyse and understand the overall setup of overburdening created by these conditions. Based on new French and Congolese archival resources, it discusses the effects of this overburdening, linking it to the responses shown by local populations, notably through flight and evasion. In a last step, the discussion focuses on the role of intermediaries and their impact on the violence that was locally experienced. The analysis includes a wider perspective into the changes and continuities during the years of World War II, and on the challenges for the forced labour system due to its official abolition in 1946 and the decline of clandestine practices of continuity until 1948.